2018
DOI: 10.15243/jdmlm.2018.052.1077
|View full text |Cite
|
Sign up to set email alerts
|

ASGM status in West Nusa Tenggara Province, Indonesia

Abstract: Artisanal Small-Scale Gold Mining (ASGM) obviously contributes to serious environmental and health issue for miners, nearby populations, and larger community when the use of mercury (Hg) occurs. Mercury amalgamation is used as a gold recovery technique by 10-12 million ASGM miners around the world and a predicted around 1000 tonnes of mercury are discharged into the environment every year as a result of poor mining practices. Exposure to mercury can cause serious health effects for future generation, and miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…This period was much shorter than the 14.8 years needed to show specific clinical manifestations in previous reports 13. Krisnayanti found similar evidence of mercury exposure around Taliwang ASGM activities where the mean concentrations of mercury in hair of exposed, indirectly exposed and non-exposed groups were 13, 1.3 and 0.56 μg/g, respectively 14. The ASGM sector in Taliwang has a large migrant worker population, which is an important economic support to the local community, but ASGM activities involve high mercury use and illegal mercury trading.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This period was much shorter than the 14.8 years needed to show specific clinical manifestations in previous reports 13. Krisnayanti found similar evidence of mercury exposure around Taliwang ASGM activities where the mean concentrations of mercury in hair of exposed, indirectly exposed and non-exposed groups were 13, 1.3 and 0.56 μg/g, respectively 14. The ASGM sector in Taliwang has a large migrant worker population, which is an important economic support to the local community, but ASGM activities involve high mercury use and illegal mercury trading.…”
Section: Introductionsupporting
confidence: 66%
“…In contrast, ASGM activities in Taliwang began in 2010, and mining activity has gradually increased without signs of stopping compared to Sekotong. In 2013, there were around 5000 trommel (using 250–500 gram of mercury/trommel) and 95 cyanidation tanks involving around 15,380 miners 14…”
Section: Methodsmentioning
confidence: 99%
“…Over 45% of East and South Kalimantan has been allocated for mining, mostly for coal, and between 2009 and 2011 one-quarter of all deforestation in Kalimantan was due to the clearance of forest within coal-mining concessions (53). ASGM is also a growing threat to Indonesia’s forests, with approximately one million ASGM miners across the archipelago (54, 55), with particular concentrations in conservation areas. The strategic environmental assessment of Indonesia’s 2011–2025 development strategy, based on infrastructure and natural-resource extraction concluded that the strategy could put US$490 billion of natural capital at risk annually, although actual impacts were deemed likely to be lower (56).…”
Section: Resultsmentioning
confidence: 99%
“…Sungai ini melalui beberapa kabupaten di dua provinsi tersebut. Salah satu kabupaten yang dilalui adalah Kabupaten Darmasraya yang merupakan wilayah dengan aktifitas pertambangan emas tradisional yang relatif tinggi [12], [13] [26]. Penelitian [25] di Bombana, Sulawesi Tenggara bahkan menyebutkan bahwa pendapatan PESK di Bombana lebih tinggi daripada pendapatan PESK di Jawa, serta lebih tinggi daripada pendapatan masyarakat yang bekerja pada sektor lain di Bombana.…”
Section: Pendahuluanunclassified